Oestrous synchronization using composite solution of testosterone, oestradiol and progesterone on Peranakan Etawah goat - Sutama, I-Ketut; Dharsana, R; Budiarsana, I-G.M; Kostaman, T (Indonesian Animal Sciences Society, 2002)
Progestagen is generally used for hormonal treatment in the synchronization program, but the cost of this stuffs is relatively expensive. An alternatif low cost agent for sinchronization is needed and this is a focus of the present study. Forty eight heads of mature does and 4 bucks of Peranakan Etawah (PE) goats was used in two phases of study. In the first phase, three types of composite compounds (TOP-A, TOP-B and TOP-C) were tested on a number of PE does. In the second phase of the study, the best TOP composite of the first phase was compared with Fluogestone Acetate (FGA) which is a commercially made of progestagen for synchronization. FGA was inserted intravaginal for 7 days (FGA-7) and 14 days (FGA-14). Results of the study in phase I showed that only 40-60% of does showed oestrus following TOP composite treatment, and 50-67% of them in groups TOP-A and TOP-B did not ovulate, while all oestrous does in TOP-C group ovulated. Oestrous cycle length was within a normal range of oestrous cycle (15 - 22 days) indicating that TOP composite did not have negative effect on reproductive activity of goats. The best TOP-C in the study phase I was tested in the study phase II and compared with FGA. The results showed that the number of does in oestrus in TOP-C group was only 63.6% which was much lower than those of FGA-7 (81.8%) and FGA-14 (100% ). Imperiority of TOP-C and FGA-7 were shown by a relatively high incident of oestrus without ovulation which were 14.3% and 11.1% for the respective groups. Consequently, ovulation rates in both groups were lower than those of FGA-14 (1.1 vs 1.4 vs 1.8, P<0.05). Pregnancy rate in TOP-C was also the lowest (27.3%) compared with those of group FGA-7 (63.6%) and group FGA-14 (81.8%). Based on the results obtained, it could be concluded that TOP composite used in this study was not as good as FGA in inducing oestrus in goat. Â Key words: Oestrous synchronization, progestagen, Peranakan Etawah goat